Sustainability and Human Rights Practices and Training - Panagiotopoulos, Giorgos (European Scientific Journal, ESJ, 2024)
Twenty-first century citizens live in an interconnected, diverse and intensively changing world. Developing sustainability and human rights practices is of major importance for the survival of both the present and the future generations. This research study comes to investigate primary education teachers’ sustainability practices in their daily lives concerning the three basic pillars of sustainable development, environment, society and economy. At a second level, it is sought to investigate whether there is a correlation between teachers’ practices and their training in sustainability and human rights issues. The "Sustainability Consciousness Questionnaire", in its short version with closed-ended questions-statements was delivered, whereas its reliability and validity were positively assessed. The technique of convenient sampling process was applied, and the sample consisted of 452 primary education teachers working in the Region of Western Greece. Data were analyzed by using IBM SPSS v.28 software. Percentages, frequencies of the mean value and standard deviation were calculated. The test of normality of variables for skills was done with Kolmogorov-Smirnov, and the parametric t-Test was applied to investigate correlations. The internal consistency reliability of the questions of the sustainability practices questionnaire is satisfactory. The findings of the research indicate that the participants are sensitive towards the necessity of recycling, waste management, saving energy, respecting others, and supporting economically weaker people. Finally, it is worth mentioning that teachers who have been trained in sustainability and human rights issues show a greater positive attitude towards sustainability practices than those who have not been trained.